Concepts in enterprise resource planning - Monk, Ellen; Wagner, Bret J. (Course Technology, 2013)
This 4E reflects the latest trends and updates in ERP (Enterprise Resource Planning) software as well as introduces the basic functional areas of business and their relationships. Readers can see how integrated information systems help organizations improve business process and provide managers with accurate, consistent, and current data for making informed strategic decisions.